Enterprising rural tourism for sustainable rural development in Sri Lanka - Mohamed Aslam, Mohamed Saleem; Awang, Khairil Wahidin (EconJournals, 2015)
Diverse and fragmented socio-cultural and environmental fabrics of rural areas offer a number of tourism entrepreneurial opportunities in anticipating the diverse interest of tourists. The tourism enterprises embody different alternative tourism labels to encroach to rural areas and replace the conventional mass tourism. However prevailing tourism, development and implementation in rural landscapes do not compliance with the sustainable development criteria. The main objective of the study is to investigate enormity of the rural tourism enterprises in conjunction with SRTD process empirically. This adapted the qualitative case study approach to interpret the natural settings of socially constructed world of rural Sri Lanka. Semi-structured interviews of key informants, direct observation of community, appraisal of artefacts and field notes during the interactions in the setting supported to enrich the empirical study. Deriving thick rich descriptions through triangulated analysis of factual interpretations from multiple sources informs that inappropriate initiations and lacks in integration of stakeholders and local resources restrain development and designing of rural tourism enterprises to anticipate sustainable development challenges in Sri Lanka. Sustainable Rural Tourism Development claims the rural tourism enterprises to have rural tourism resource inventory, appropriate rural tourism product development and designing while integrating, cooperating stakeholders and local resources. Ensuring sustainability in rural tourism development envisages socio-community enterprises to contribute for sustainable rural development at large.